2013
DOI: 10.1105/tpc.113.113035
|View full text |Cite
|
Sign up to set email alerts
|

A Role for APETALA1/FRUITFULL Transcription Factors in Tomato Leaf Development  

Abstract: Flexible maturation rates underlie part of the diversity of leaf shape, and tomato (Solanum lycopersicum) leaves are compound due to prolonged organogenic activity of the leaf margin. The CINCINNATA -TEOSINTE BRANCHED1, CYCLOIDEA, PCF (CIN-TCP) transcription factor LANCEOLATE (LA) restricts this organogenic activity and promotes maturation. Here, we show that tomato APETALA1/FRUITFULL (AP1/FUL) MADS box genes are involved in tomato leaf development and are repressed by LA. AP1/FUL expression is correlated nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 119 publications
(171 reference statements)
2
67
3
Order By: Relevance
“…The suppression of the activity of FUL-like genes results in reduced leaf complexity and in a partial suppression of the phenotype caused by miR319 overexpression. Overexpression of one of the genes from this family suppressed the La gain-of-function phenotype (Burko et al, 2013). This suggests that AP1/FUL proteins promote the morphogenetic activity of the tomato leaf margin, in agreement with accumulating evidence pointing to a role for FUL-like genes in leaf development in Arabidopsis, poppy, pea and Aquilegia (Ferrandiz et al, 2000;PabonMora et al, 2012PabonMora et al, , 2013Teper-Bamnolker and Samach, 2005).…”
Section: Antagonistic Transcription Factors Affect the Balance Betweesupporting
confidence: 69%
See 1 more Smart Citation
“…The suppression of the activity of FUL-like genes results in reduced leaf complexity and in a partial suppression of the phenotype caused by miR319 overexpression. Overexpression of one of the genes from this family suppressed the La gain-of-function phenotype (Burko et al, 2013). This suggests that AP1/FUL proteins promote the morphogenetic activity of the tomato leaf margin, in agreement with accumulating evidence pointing to a role for FUL-like genes in leaf development in Arabidopsis, poppy, pea and Aquilegia (Ferrandiz et al, 2000;PabonMora et al, 2012PabonMora et al, , 2013Teper-Bamnolker and Samach, 2005).…”
Section: Antagonistic Transcription Factors Affect the Balance Betweesupporting
confidence: 69%
“…In the leaf, a high SFT/FT ratio promotes maturation, leading to a simplified leaf form. This effect is enhanced in conjunction with the trifoliate (tf ) mutant and is suppressed by miR319 overexpression (Burko et al, 2013;Shalit et al, 2009).…”
Section: Antagonistic Transcription Factors Affect the Balance Betweementioning
confidence: 97%
“…Pleiotropic effects of flowering time regulators might be a consequence of changes in source-sink relationships triggered by the transition from vegetative to reproductive growth. However, studies in Arabidopsis and tomato also suggested that FT-like genes and the downstream targets SOC1 and AP1/FUL may control the activity of leaf meristems (Teper-Bamnolker and Samach, 2005;Melzer et al, 2008;Shalit et al, 2009;Burko et al, 2013). For example, Melzer et al (2008) showed that FT and its downstream targets SOC1 and FUL controlled determinacy of leaf and axillary meristems independent of flowering time in Arabidopsis.…”
Section: The Induction Of the Photoperiod Pathway In The Leaves And Mmentioning
confidence: 99%
“…In C. hirsuta and tomato, the down-regulation of KNOXI genes results in compound leaves with reduced leaflets Shani et al, 2009;Burko et al, 2013). In tomato, overexpression of the KNOXI gene, LeT6, results in supercompound leaves (Hareven et al, 1996).…”
mentioning
confidence: 99%